Bridged cassane derivatives from the seeds of Caesalpinia sappan L. and their cytotoxic activities. (May 2022) - Jin, Yue; Wang, Miao; Yan, Yan-Fang; Zhang, Xin-Xin; Li, Xian-Zhe; Gao, Hui-Yuan
Abstract: Two undescribed nitrogen bridged cassane alkaloids (caesanamides A–B) and five undescribed oxygen bridged cassane diterpenoids (caesalpinins JA–JE), together with six known analogs, were isolated and identified from the seeds of Caesalpinia sappan . Their structures, including the absolute configurations, were unequivocally elucidated by the analysis of comprehensive spectroscopic data, ECD calculations, single-crystal X-ray diffraction and the CASE algorithm. Among them, caesanamides A and B represent the first examples of cassane alkaloids bearing unique ring systems of an amide bridge between C-19/C-20 incorporating a 1, 3-oxazolidine (6/6/6/5/6/5) or a 7-one-1, 3-oxazepine (6/6/6/5/6/7). Caesalpinin JA is an A/B cis -20-norcassane diterpenoid with a rare five-membered oxygen bridge between C-10/C-18. Biological evaluation showed that cassane alkaloids exhibited significant cytotoxicity against HepG2 cells with IC50 values of 13.48 ± 1.07 μ M (caesanamide A), 18.91 ± 0.98 μ M (caesanamide B), and 7.82 ± 0.65 μ M (caesanine B). Further flow cytometry analysis revealed that caesanine B could cause G0G1 cell cycle arrest and promote apoptosis in a dose- and time-dependent manner in HepG2 cells. Graphical abstract: Image 1 Highlights: Seven undescribed and six known cassane compounds isolated from Caesalpinia sappan. Two cassane alkaloids possess rare 6/6/6/5/6/5 and 6/6/6/5/6/7 ring systems. Cassane alkaloids exhibited significant cytotoxic effects against HepG2 cells. Caesanine B induced apoptosis and arrested G0G1 phase cycle in HepG2 cells.